Sufistic Nature Contemplation (Tadabbur Alam) in Islamic Guidance and Counseling: Enhancing Psychological Flexibility in Higher Education Students - Hariastuti, Retno Tri; Ratnasari, Devi; Ariyanto, Restu Dwi; Naqiyah, Najlatun; Winingsih, Evi; Nuryono, Wiryo; Habsy, Bakhrudin All (Bumi Publikasi Nusantara, 2026)
Psychological flexibility is essential for university students to adapt and succeed in developmental and academic challenges. This study examines the effectiveness of an Islamic guidance and counseling framework based on sufistic tadabbur alam (nature contemplation) in enhancing students’ psychological flexibility. A pre-experimental one-group pretest-posttest design was employed with nine fourth-semester students at Universitas Negeri Surabaya, selected through purposive sampling. The intervention included contemplative activities grounded in Sufi values and nature reflection, with a 60-item flexibility scale developed from the works of Al-Ghazali, Ibn Sina, and Ibn Arabi. Analysis using the Wilcoxon Signed Rank Test revealed a significant increase in psychological flexibility across cognitive, emotional, and behavioral dimensions. These findings support the integration of spiritual and ecological elements into counseling models to foster resilience and self-awareness. This study contributes to Islamic educational psychology by offering a holistic and spiritually grounded approach to student well-being and personal development.